2014
DOI: 10.19173/irrodl.v15i6.1928
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality and chronotype on distance learning willingness and anxiety among vocational high school students in Turkey

Abstract: There are many studies related to distance learning. Willingness and anxiety are important variables for distance learning. Recent research has shown that anxiety and willingness towards distance learning are moderated by personality. This study sought to investigate whether distance learning willingness and distance learning anxiety are associated with age, gender, occupation, chronotype and personality in a Turkish vocational high school students sample. Two measures of individual differences were implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…Many empirical studies have shown the advantages of short questionnaires over long questionnaires in terms of effective response rate (Harris, 1997;Salisbury et al, 2005). Third, previous studies (e.g., Keller & Karau, 2013;Randler et al, 2014;Van Bragt, Bakx, Bergen, & Croon, 2010) explored the relationship between personality types and perceptions towards online learning; however, most of their survey constructs did not address the design features of online courses. For instance, the studies by Keller and Karau (2013) and Randler et al (2014) are similar to each other; they focus mainly on acceptance/willingness and anxiety of students towards online learning.…”
Section: The Need For This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Many empirical studies have shown the advantages of short questionnaires over long questionnaires in terms of effective response rate (Harris, 1997;Salisbury et al, 2005). Third, previous studies (e.g., Keller & Karau, 2013;Randler et al, 2014;Van Bragt, Bakx, Bergen, & Croon, 2010) explored the relationship between personality types and perceptions towards online learning; however, most of their survey constructs did not address the design features of online courses. For instance, the studies by Keller and Karau (2013) and Randler et al (2014) are similar to each other; they focus mainly on acceptance/willingness and anxiety of students towards online learning.…”
Section: The Need For This Studymentioning
confidence: 99%
“…Third, previous studies (e.g., Keller & Karau, 2013;Randler et al, 2014;Van Bragt, Bakx, Bergen, & Croon, 2010) explored the relationship between personality types and perceptions towards online learning; however, most of their survey constructs did not address the design features of online courses. For instance, the studies by Keller and Karau (2013) and Randler et al (2014) are similar to each other; they focus mainly on acceptance/willingness and anxiety of students towards online learning. These constructs are not helpful in terms of the design perspective (i.e., how to design online courses to minimise problems and accommodate different personality traits).…”
Section: The Need For This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the development of an MLE, we also considered several key thinking styles (e.g., those most relevant to students engaged in mobile learning), which have been described as contributing to achieving learning goals more effectively (Dunn & Honigsfeld, 2013; Fan & Zhang, 2014; Ford, 1985, 1995, Pask, 1976, 1988; Schmeck, 1988; Witkin, Moore, Goodenough, & Cox, 1977), and gender differences. Both elements were examined to better ensure that the mediated experience was relevant to the students participating in mobile learning.…”
Section: Introductionmentioning
confidence: 99%